1974
DOI: 10.1111/j.1432-1033.1974.tb03800.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Metabolic Effects Induced in the Rat by a High-Fat Diet. Control of Glucose Metabolism in Adipose Tissue of Fed and Fasted Rats

Abstract: Epididymal adipose tissue of rats fed a high-fat diet and submitted or not to a 24-h fast before the experiment, was incubated with 10 mM glucose labelled with 14C at C-6, C-1 or universally, in the presence of insulin (1000 yU/ml). The results were used to estimate the glucose carbon flow through the various metabolic pathways and to establish a balance of production and utilization of reducing equivalents in the cytoplasmic compartment.Although previously altered by the fat diet, glucose metabolism is shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…After the CCGG-0.5X, CCGG-1X, and CCGG-2X supplementation were markedly decreased 23.7 % ( P = 0.0006), 23.1 % ( P = 0.0008), and 32.5 % ( P < 0.0001) compared to the HED rats without treatment. Recent studies showed that feeding rats with a high-fat diet induced the changes in several enzymatic reactions related to carbohydrate metabolism in liver and adipose tissue [ 22 , 23 ]. Thus, it supported the possibility that CCGG may have an alternation on several enzymatic reactions and reduce the formation of adipose tissue.…”
Section: Resultsmentioning
confidence: 99%
“…After the CCGG-0.5X, CCGG-1X, and CCGG-2X supplementation were markedly decreased 23.7 % ( P = 0.0006), 23.1 % ( P = 0.0008), and 32.5 % ( P < 0.0001) compared to the HED rats without treatment. Recent studies showed that feeding rats with a high-fat diet induced the changes in several enzymatic reactions related to carbohydrate metabolism in liver and adipose tissue [ 22 , 23 ]. Thus, it supported the possibility that CCGG may have an alternation on several enzymatic reactions and reduce the formation of adipose tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Pilkis (1970) showed that the major source of G6P in white adipose cells is neither glycogen nor gluconeogenic precursors but blood glucose. Further, the rate of lipid synthesis is low in the white adipose tissue of starved rats (Zaragoza-Hermans, 1974). Therefore, the intracellular concentration of G6P is probably relatively high in white adipose cells from starved animals.…”
Section: Discussionmentioning
confidence: 96%
“…Glucose thus produced may be released into the blood. In starved animals, however, the greater part of blood glucose is produced in the liver from lactate and alanine derived from the skeletal muscle (Felig et al, 1970;Kusaka and Ui, 1977), and from fatty acids derived from white and brown adipose tissues (Zaragoza-Hermans, 1974;Nedergaard and Lindberg, 19821, and is from liver glycogen (Kanamura et al, 1980). The role of glucose released directly from brown adipose cells, even if present in small amounts, is possibly to elevate the glucose level, which inclined to be low in the blood of mice starved for 3 days.…”
Section: Discussionmentioning
confidence: 99%
“…also considerable recycling of fructose 6-phosphate t at zero time: through the pentose phosphate cycle as suggested for bovine adipose tissue from the relative rates of 14CO2 production from [6-14C]and [2-14C]-glucose (Baldwin et al, 1973). The pattern of glucose metabolism in ruminant adipose tissue thus differs markedly from that of the rat (Flatt & Ball, 1964, 3h tissue at zero Saggerson & Greenbaum, 1970;Zaragozation of pieces of Hermans, 1973, 1974). nedium resulted…”
Section: Discussionmentioning
confidence: 99%